Integration, resumption, and juxtaposition: The relation between Early New High German preposed adverbial clauses and their host - Bloom, Barthe (Glossa: a journal of general linguistics, 2024)
In Early New High German, preposed adverbial clauses could be juxtaposed, resumed, or fully integrated into their host sentence. This is thought to be representative of a continuum and a diachronic development of clause-integration. The current study evaluates this diachronic continuum by testing predictions that follow from it by statistically evaluating the distinctiveness between the patterns, focusing on the adverbials’ function within the host sentence and their role in the narrative structure. It is thereby the first study on this issue to systematically analyze data from a larger corpus of narrative texts. The results find first support that what has been called adverbial resumption is not a unified phenomenon. Instead patterns with da ‘then’ and patterns with so ‘so’ should be distinguished: The former is associated with narrative summaries and tends to combine with sentences introduced by da or als, expressing temporal simultaneity and sequence; the latter occurs predominantly with V1-clauses and with clauses introduced by the conjunctions ob, so and wann, is used to introduce alternative events, and is not associated with the rapid temporal progression of the story. The results indicate a high degree of functional and contextual similarity between integration and da-resumption, which supports a diachronic development of da-resumed adverbial clauses into integrated ones. This is not the case for so-resumption. Finally, juxtaposition turns out to be highly similar to the pattern with so and has not developed its own niche. The results support a competition scenario between integrated adverbial clauses and those resumed by da but not with patterns with so. As such, the study paints a more detailed picture of the continuum of clausal integratio
Keywords: Early New High German; adverbial clauses; clause-integration; narrative structure; paradigmatic relations